Molecular characterization of Enterobacteriaceae resistant to carbapenem antimicrobials - Jaciane B. Marques; Pauline C. Bonez; Vanessa A. Agertt; Vanessa C. Flores; Tanise V. Dalmolin; Grazielle G. Rossi; Nara Lucia F. Dal Forno; Bianca V. Bianchini; Caren R. Mizdal; Fallon S. Siqueira; Roselene A. Righi; Bettina H. Meneghetti; et al. (Sociedade Brasileira de Patologia Clínica, 2015)
ABSTRACT The present study aimed to genotypically and phenotypically characterize clinical isolates of carbapenem-resistant Enterobacteriaceae collected from inpatients at the University Hospital of Santa Maria, during seven months. Among the clinical isolates subjected to the modified Hodge test (MHT), 62.5% were positive, indicating possible production of carbapenemase. Polymerase chain reaction (PCR) demonstrated that blaKPC was the most frequently found gene (31%), followed by blaIMP (12.5%). Combined use of the methods is needed to identify carbapenem resistance in enterobacteria to prevent their spread and control the infections caused by these organisms.